INSTRUMENT DEVELOPMENT OF POLITICAL PARTY INSTITUTIONALIZATION INDEX: A PRELIMINARY STUDY - Sweinstani, Mouliza K.D; Siregar, Sarah Nuraini; Ekawati, Esty; Noor, Firman; Hanafi, Ridho Imawan; Muntafa, Farhan (CosmoGov: Jurnal Ilmu Pemerintahan, 2024)
Several qualitative studies on party institutionalization done previously in Indonesia have not provided measurement instruments to asses the degree of party institutionalization comprehensively. The purpose of this study is to complement and strengthen the analysis of party institutionalization, which has been analyzed before. By using quantitative approach with the Confirmatory Factor Analysis (CFA) technique, the authors elaborated the four dimensions of party institutionalization by Randall and Svasand into several sub dimensions-Subsub dimension, variable and indicators which are relevant to Indonesia political parties. The authors then validated the instrument constructed by content validity method using expert judgement which is still on going. Therefore, as the preliminary study, the instrument provided here is still need further improvement by forming a construct that will perfect the entire CFA method and comprehensively produce the whole instrument of political party institutionalization index.